Post‐operative complications in elderly onset inflammatory bowel disease: a population‐based study. Issue 12 (8th May 2018) - Sacleux, S.‐C.; Sarter, H.; Fumery, M.; Charpentier, C.; Guillon‐Dellac, N.; Coevoet, H.; Pariente, B.; Peyrin‐Biroulet, L.; Gower‐Rousseau, C.; Savoye, G.; ,
Summary: Background: IBD diagnosed after the age of 60 is increasing. Data on post‐operative complications in elderly onset IBD are scarce. Aim: To describe the incidence of and factors associated with post‐operative complications in elderly onset IBD, diagnosed after the age of 60. Methods: Using EPIMAD Cohort (1988‐2006), among 841 incident IBD patients, 139 (17%) underwent intestinal surgery, including 100 Crohn's disease (CD) and 39 ulcerative colitis (UC). Results: After a median post‐operative follow‐up of 6 years (2‐10), 50 (36%) patients experienced at least 1 complication with a total of 69. During the first 30 post‐operative days, the mortality rate was 4%. Thirty‐two early complications (<30 days) were observed in 23 patients (17%), with 15 infectious, without significant difference between CD and UC. More than half early post‐operative complications (n = 19, 59%) were severe (>grade 2) without significant difference between CD and UC ( P = 0.28). Thirty‐seven long‐term adverse effects of surgical therapy (≥30 days) were observed in 33 patients (24%). Multivariate analysis found (1) acute severe colitis (OR = 7.84 [2.15‐28.52]) and emergency surgery (OR = 4.46 [1.75‐11.36]) were associated with early post‐operative complications, and (2) Female gender (HR = 2.10 [1.01‐4.37]) and delay before surgery >3 months (HR = 2.09 [1.01‐4.31]) with long‐term adverse effects of surgical therapy. Conclusions: One‐third of elderly IBD patients experienced at least 1 post‐operative complication. Half of the early complications were severe, and infectious. Emergency surgery was the key driver for post‐operative complication. Abstract : Linked Content This article is linked to Myrelid and Savoye et al papers. To view these articles visithttps://doi.org/10.1111/apt.14833 andhttps://doi.org/10.1111/apt.14854 .